2020
DOI: 10.1002/pc.25663
|View full text |Cite
|
Sign up to set email alerts
|

On the machining behavior of carbon fiber reinforced polyimide and PEEK thermoplastic composites

Abstract: Polyimide (PI) and polyetheretherketone (PEEK) are superior high‐performance thermoplastics being extensively used in the fields of fiber‐reinforced polymer composites. However, there is very limited literature addressing the machining behavior of the PI and PEEK composites. The present paper aims to conduct a comparative study into the machining characteristics of these two representative high‐performance thermoplastic matrix composites under varying cutting conditions. Machinability aspects of the carbon/PI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 43 publications
5
57
0
Order By: Relevance
“…They found that the induction-processed composite material produced equivalent or better holes than the autoclave-processed composites. J. Xu et al [ 17 ] compared the drilling performance of carbon/PEEK and carbon/polyimide (PI) composites. They confirmed that when drilling the carbon/PEEK composites, higher drilling forces and higher cutting temperature occurred compared with carbon/polyimide composites, indicating poor machinability.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the induction-processed composite material produced equivalent or better holes than the autoclave-processed composites. J. Xu et al [ 17 ] compared the drilling performance of carbon/PEEK and carbon/polyimide (PI) composites. They confirmed that when drilling the carbon/PEEK composites, higher drilling forces and higher cutting temperature occurred compared with carbon/polyimide composites, indicating poor machinability.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoset plastic-based carbon-epoxy composite provided higher cutting forces and temperature. Drilling comp a r i s o n o f c a r b o n -p o l y a m i d e a n d c a r b o n -Polyetheretherketone shows that carbon/Peek system has high tool wear in the form of abrasion and adhesion [19]. Drilling comparison between brad spur drill, twist drill, and dagger drill showed better performance of brad spur drill [20].…”
Section: Introductionmentioning
confidence: 95%
“…Although, many studies using laser processing for industrial applications of CFRP have been reported, most experimental works have focused on the machining of thermoset CFRP using infrared laser wavelength. For the environmental aspect of recycling, a systematic machining study of thermoplastic CFRP is also potentially important for CFRP reuse [ 5 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%